[Hot Water Conduits and Sheep Near Reykjavik] - Streng, Evelyn Fiedler (1975)
Photograph of hot water conduits running along sheep and a road to Reykjavik, Iceland. Two stone walls, one dark on the right and the other white, sit along a grassy hill parallel to a road visible along the left edge of the photograph. A flat mountain is visible in the background, power lines running ahead of it. A group of white and black sheep stand on the hill beside a wire fence to the right.